Human Resource Management Strategies on Crew Turnover at Al Mutawa Marine Work L.L.C – Case Study in Abu Dhabi - Roni, Roni; Iqbal, Mohammad Ali (International Journal of Social and Management Studies, 2025)
This study aims to analyze the human resource management strategy and identify the main factors that cause high turnover of crew employees at Al Mutawa Marine Work L.L.C in Abu Dhabi – United Arab Emirates. The participants of this study were crewing managers or marine advisors, crewing officers, senior crew employees and new crew employees totaling 4 people, using a qualitative approach and field data collection methods through interviews with key informants, observation of research objects and documentation studies in accordance with the theme being studied, then analysis was carried out using NVivo 12 software tools. The results of the study indicate that the company’s management strategy in overcoming employee turnover focuses on evaluation and flexibility of policies and crew employee retention management that adjusts human resource regulations, optimizes contract policies, and evaluates the human resource management system periodically. Other factors that play a role are effective communication between management and crew employees and the provision of a clear career path. These findings are expected to provide recommendation for companies in increasing employee retention and reducing turnover rates in the future. The implications of this study are discussed in the article.